Maintenance of HDACs and H3K9me3 Prevents Arterial Flow-Induced Venous Endothelial Damage - Wang, Ting-Yun; Chang, Ming-Min; Li, Yi-Shuan Julie; Huang, Tzu-Chieh; Chien, Shu; Wu, Chia-Ching (Frontiers in Cell and Developmental Biology, 2021)
The transition of flow microenvironments from veins to arteries in vein-graft surgery induces “peel-off” of venous endothelial cells (vECs) and results in restenosis. Recently, arterial laminar shear stress (ALS) and oscillatory shear stress (OS) have been shown to affect the cell cycle and inflammation through epigenetic controls such as histone deacetylation by histone deacetylases (HDACs) and trimethylation on lysine 9 of histone 3 (H3K9me3) in arterial ECs. However, the roles of H3K9me3 and HDAC in vEC damage under ALS are not known. We hypothesized that the different responses of HDACs and H3K9me3 might cause vEC damage under the transition of venous flow to arterial flow. We found that arterial ECs showed high expression of H3K9me3 protein and were retained in the G0 phase of the cell cycle after being subjected to ALS. vECs became round under ALS with a decrease in expression of H3K9me3, HDAC3, and HDAC5, and an increase in expression of vascular cell adhesion molecule 1 (VCAM-1). Inhibition of HDACs activity by a specific inhibitor, phenylbutyrate, in arterial ECs caused similar ALS-induced inflammation and cell loss as observed in vECs. Activation of HDACs and H3K9me3 by ITSA-1, an HDAC activator, could prevent ALS-induced peel-off and reduced VCAM-1 expression in vECs. Moreover, shear stress modulates EC morphology by regulation of focal adhesion kinase (FAK) expression. ITSA-1 could increase phosphorylated (p)-FAK expression in vECs under ALS. We found that perturbation of the activity of p-FAK and increase in p-FAK expression restored ALS-induced H3K9me3 expression in vECs. Hence, the abnormal mechano-responses of H3K9me3 and HDAC in vECs after being subjected to ALS could be reversed by ITSA-1 treatment: this offers a strategy to prevent vein-graft failure.